Physiology of Pancreas in View of Diabetes Mellitus, Classification and Diagnostic Criteria of Diabetes Mellitus - Aditi Goyal; Samarth Shukla (A Concise Clinicopathological Handbook of Diabetes Mellitus, 2021)
Diabetes Mellitus is a complex disorder. It affects various organ systems of the body. Insulin is the key regulator of glucose metabolism along with other hormones. This chapter will discuss the key concepts of the physiological aspects of pancreas as an endocrine organ and physiology of Insulin secretion and action in maintaining blood glucose levels. This chapter also will discuss the physiologic concepts of development of Diabetes along with the classification and diagnostic criteria of Diabetes Mellitus.